Auditoría informática al área de control de la gestión de la empresa Multipropósito de Calarcá S.A. E.S.P. (2013)
This research project involves the development of a Computer Audit at six (6) elements Area Information System mentioned, such as the Hardware, Software, Users, Data, Processes and Physical Plant, clarifying that the conduct of an audit as it is given by the absence of a similar process in the area, initially effected theoretical research and rules in order to be clear about the main aspects to consider in this type of audit, as well as key standards in its development. Subsequently established a number of features, which are raised in the scope of the audit, and allow information about each of the above items. Additionally plotted targets, which are based on the examination, analysis, verification and identification of aspects such as processes, appropriate use of information resources, controls, procedures, compliance and risk identification, to finally reach the determination of conclusions and recommendations, and likewise to learn the process, you create a series of questionnaires and surveys, which mixed with the observation, personal interviews with members of the area and the use of CAAT, allow to structure the audit. Finally, after analyzing all the information, identifies a number of risks, which are consolidated in a matrix, which explains its effects on the area, and recommendations that can be implemented to reduce them.